Metabolic enzyme activities in relation to crowding stress in the wedge sole (Dicologoglossa cuneata). (4th April 2014) - Herrera, Marcelino; Ruiz‐Jarabo, Ignacio; Vargas‐Chacoff, Luis; de la Roca, Elena; Mancera, Juan M
Abstract In this work, we have assessed the effects of different stocking densities on the biometry, survival and physiological status of the wedge sole (Dicologoglossa cuneata), focusing on changes in the stress system and intermediate metabolism, with the aim of determining a stress indicator for chronic‐stress situations in this species. Wedge sole were kept at three different stocking densities (0.2, 0.4 and 0.8 kg m−3) for 197 days, and survival, growth, plasma metabolites, cortisol and enzymatic activities were assessed. Survival rates were the highest at low density, though growth did not vary significantly among treatments. Enzymatic activities, mainly in muscle, differed depending on stocking density. Liver hexokinase activity at low stocking density was the highest, while no differences were detected for the other enzymes assessed. In muscle, all enzymes significantly increased in activity with stocking density. We concluded that long‐term high stocking density culture significantly changed enzyme activities (hexokinase, glutamate dehydrogenase, glyceraldehyde 3‐phosphate dehydrogenase, and lactate dehydrogenase) in wedge sole muscle, although liver enzymes, plasma cortisol and metabolites did not vary significantly. Therefore, muscle enzymes, hexokinase and glutamate dehydrogenase, could be considered stress indicators for this species in chronic‐stress situations.